The Diagnostic Sensitivity for Ulnar Neuropathy at the Elbow Is Not Increased by Addition of Needle EMG of ADM and FDI When Nerve Conduction Studies Are Normal - Kurver, Anne; Smolders, Joost; Verhagen, Wim I. M.; Meulstee, Jan; Nijhuis, Frouke A. P. (Frontiers in Neurology, 2019)
Introduction: The main objective of this study was to investigate whether electromyography (EMG) has additional value in the confirmation of the clinical diagnosis of ulnar nerve entrapment at the elbow (UNE) if nerve conduction studies (NCS) are normal. Methods: A prospective cross-sectional cohort observational study was conducted among patients with the clinical suspicion of UNE. A total of 199 arms of 166 subjects were included, who were all examined according to a standard neurophysiological protocol, i.e. NCS and EMG relevant to the ulnar nerve. Results: NCS were normal in 76 (38.2%) arms. No abnormal spontaneous muscle fiber activity was found with EMG in any of these cases. . In 9 arms with normal NCS (11.8%), isolated abnormal MUAP configurations were found with EMG. Of these nine arms one UNE was diagnosed clinically, in which additional ultrasound and repeated NCS/EMG was negative. One had already been diagnosed with neuralgic amyotrophy and one with CTS. The other 6 arms had additional diagnostics which did not reveal an UNE. Conclusion: EMG as part of the standard neurophysiological protocol exclusively in the confirmation of the clinical diagnosis of UNE has no limited added value if NCS are normal. Removing EMG as a standard part of the neurophysiological protocol exclusively in a high prior-odds setting. However removing EMG will limit the burden for patients as well as the costsmay prevent detecting concomitant and/or additional differential diagnoses..